2005
DOI: 10.1254/jphs.fp0050578
|View full text |Cite
|
Sign up to set email alerts
|

FK614, a Novel Peroxisome Proliferator-Activated Receptor γ Modulator, Induces Differential Transactivation Through a Unique Ligand-Specific Interaction With Transcriptional Coactivators

Abstract: Abstract. Peroxisome proliferator-activated receptor γ (PPARγ) is a ligand-dependent transcriptional factor implicated in regulating adipogenesis, glucose homeostasis, and in mediating the action of the insulin sensitizing anti-diabetic thiazolidinedione (TZD) compounds. [3-(2,4-Dichlorobenzyl)-2-methyl-N-(pentylsulfonyl)-3-H-benzimidazole-5-carboxamide] (FK614) is a structurally novel PPARγ agonist that demonstrates potent anti-diabetic activity in vivo. Herein, we describe that FK614 is a selective PPARγ lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…This differential result could be due to the conformational changes of the PPARc LBD induced by ligands unveiling a dynamic response of the receptor. Finally, recent studies have shown that, upon binding of specific ligands, the interactions between PPARc and coregulators often depend on their amount present in a given cell, explaining why a ligand can function as a partial or full agonist [59][60][61]. On the basis of these considerations, it is tempting to speculate that the differential binding of cladosporol A and B (more specifically, 2A and 2B) to PPARc may influence the choice of coregulators through conformational changes induced onto the LBD that may account for the different pathways they regulate.…”
Section: Discussionmentioning
confidence: 99%
“…This differential result could be due to the conformational changes of the PPARc LBD induced by ligands unveiling a dynamic response of the receptor. Finally, recent studies have shown that, upon binding of specific ligands, the interactions between PPARc and coregulators often depend on their amount present in a given cell, explaining why a ligand can function as a partial or full agonist [59][60][61]. On the basis of these considerations, it is tempting to speculate that the differential binding of cladosporol A and B (more specifically, 2A and 2B) to PPARc may influence the choice of coregulators through conformational changes induced onto the LBD that may account for the different pathways they regulate.…”
Section: Discussionmentioning
confidence: 99%
“…A conceptual model of PPARg function is emerging that offers some insight into how SPPARgMs may tune PPARg to produce selective effects . The binding of a particular ligand (or no ligand) by PPARg produces a unique equlibria of conformations and dynamics that favors/disfavors interaction with a particular set of protein kinases, ubiquitin ligases, or coregulators, thus producing ligand-specific transcriptional effects (Oberfield et al, 1999;Rocchi et al, 2001;Fujimura et al, 2005;Pascual et al, 2005;Burgermeister et al, 2006;Kim et al, 2006c;Motani et al, 2009;Choi et al, 2010). Many of the SPPARgMs do show distinct cofactor binding from rosiglitazone or pioglitazone; however, the right combination of coregulator recruitment necessary for desired physical effects remains unclear.…”
Section: B Peroxisome Proliferator-activated Receptor G Functionmentioning
confidence: 99%
“…Indeed, our observation that substitution of the AP-1 binding site only partially impaired the inhibitory effect is consistent with the notion that MPBD targets multiple cis elements. Therefore, our finding that MPBD inhibits MMP-9 expression by antagonizing the AP-1 function adds a new function to the benzimidazole family of compounds that also inhibit the activity of casein kinase II, topoisomerase I, or peroxisome proliferator-activated receptor-␥ at a concentration range similar to MPBD (Rangarajan et al, 2000;Fujimura et al, 2005;Tapia et al, 2006).…”
Section: Downloaded Frommentioning
confidence: 84%